STRATEGI PEMENANGAN KAMPANYE POLITIK PASANGAN BENYAMIN DAVNIE DAN PILAR SAGA ICHSAN DALAM PILKADA TANGERANG SELATAN TAHUN 2020 - Clarisa Arfiandani (2022)
This study examines the political campaign carried out by the pair Benyamin Davnie and Pilar Saga Ichsan in the 2020 South Tangerang Pilkada. The simultaneous regional elections in 2020 are a political agenda held in South Tangerang City in the midst of the Covid-19 pandemic. Political communication has an important role in bringing Benyamin Davnie and Pilar Saga Ichsan to victory as Mayor and Deputy Mayor of South Tangerang. The success in using political communication can be seen from the successful political campaign strategies carried out through segmentation, branding, and positioning. The method used in this research is descriptive qualitative using primary data and secondary data. Descriptive qualitative research tries to describe all sources to get accurate data. The things that determine this type of descriptive research are data taken through interviews and available documents. The final results of this study indicate that the success of Benyamin Davnie and Pilar Saga Ichsan political campaigns was influenced by Benyamin Davnie achievements during his two terms as Deputy Mayor. The figure of Benyamin Davnie is very influential in his branding and positioning. Benyamin Davnie and Pilar Saga Ichsan campaign is said to be effective because it uses political communication as a reference, this can be seen when conducting face to face campaigns and utilizing social media. Keywords: South Tangsel Regional Election 2020, Political Communication, Political Campaign